Making rights a reality? : disability rights activists and legal mobilization - Vanhala, Lisa, 1979- (Cambridge ; New York : Cambridge University Press, 2011)
"Making Rights a Reality? explores the way in which disability activists in the United Kingdom and Canada have transformed their aspirations into legal claims in their quest for equality. It unpacks shifting conceptualizations of the political identity of disability and the role of a rights discourse in these dynamics. In doing so, it delves into the diffusion of disability rights among grassroots organizations and the traditional disability charities. It then shows how the diffusion of this rights model of disability can explain how and why disability activists have deployed legal strategies in pursuit of their goals. The book draws on a wealth of primary sources including court records and campaign documents and encompassing interviews with more than sixty activists and legal experts. While showing that the disability rights movement has had a significant impact on equality jurisprudence in two countries, the book also demonstrates that the act of mobilizing rights can have consequences, both intended and unintended, for social movements themselves"--Provided by publisher.
Introduction : Legal mobilization and accommodating social movements -- Rights and political identity in the Canadian disability movement -- Disability equality and opportunity in the Supreme Court of Canada -- Disability organizations and the diffusion of rights in the United Kingdom -- Framing disability equality in the UK courts -- Conclusions : Litigation, mobilization and social movements.
Includes bibliographical references (pages 273-281) and index.
Keywords: People with disabilities -- Legal status, laws, etc. -- Great Britain -- History; People with disabilities -- Great Britain -- History; People with disabilities -- Legal status, laws, etc. -- Canada -- History; People with disabilities -- Canada -- History; People with disabilities; People with disabilities -- Legal status, laws, etc; People with disabilities -- Legal status, laws, etc. -- Great Britain -- History; People with disabilities -- Great Britain -- History; People with disabilities -- Legal status, laws, etc. -- Canada -- History; People with disabilities -- Canada -- History; Canada; Great Britain; History